Motivation the key success in teaching and learning - Johnson, Todd; Brittner, Ilana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2003)
This programs shared the motivational information for learners as a key to success in teaching and learning. Its includes motivationally instruction, classrooms and schools
tape 1. Motivationally anchored instruction (37 min.) -- tape 2. Motivationally anchored classrooms (30 min.) -- tape 3. Motivationally anchored schools (29 min.)
Title from title screen
Editor, Ilana Brittner, Dave Brittner ; graphics, Dee Gee ; director of photography, Dave Brittner
Keywords: Motivation in education; Achievement motivation